Potentiation of Calcium Influx and Insulin Secretion in Pancreatic Beta Cell by the Specific TREK-1 Blocker Spadin - Céline Hivelin; Sophie Béraud-Dufour; Christelle Devader; Amar Abderrahmani; Sébastien Moreno; Hamid Moha ou Maati; Alaeddine Djillani; Catherine Heurteaux; Marc Borsotto; Jean Mazella; Thierry Coppola (Journal of Diabetes Research)
Inhibition of the potassium channels TREK-1 by spadin (SPA) is currently thought to be a promising therapeutic target for the treatment of depression. Since these channels are expressed in pancreatic β-cells, we investigated their role in the control of insulin secretion and glucose homeostasis. In this study, we confirmed the expression of TREK-1 channels in the insulin secreting MIN6-B1 β-cell line and in mouse islets. We found that their blockade by SPA potentiated insulin secretion induced by potassium chloride dependent membrane depolarization. Inhibition of TREK-1 by SPA induced a decrease of the resting membrane potential (ΔVm~12 mV) and increased the cytosolic calcium concentration. In mice, administration of SPA enhanced the plasma insulin level stimulated by glucose, confirming its secretagogue effect observed in vitro. Taken together, this work identifies SPA as a novel potential pharmacological agent able to control insulin secretion and glucose homeostasis.